Hollow Co3O4@MnO2 Cubic Derived From ZIF-67@Mn-ZIF as Electrode Materials for Supercapacitors - Xu, Jiani; Xu, Chaoting; Zhao, Yanhong; Wu, Jianghong; Hu, Junqing (Frontiers in Chemistry, 2019)
Hollow Co3O4@MnO2 cubic nanomaterials are synthesized by ZIF-67@Mn-ZIF sacrificial precursor through a facile thermal treatment. As a kind of supercapacitor electrode material, it demonstrates high performances such as specific capacitance of 413 F g-1 at the current density of 0.5 A g-1, as the current densities raised from 0.5 to 10 A g-1 (20 times increasing), there still have approximately 41% retention of its initial capacitance. These satisfactory electrochemical properties should be put down to the hollow and porous structure and the relative higher BET surface area, which supplies more reactive sites for charge and discharge processes.